Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric device
Through the primary sintering treatment, the nickel-manganese hydroxide precursor, the titanium source, the lanthanum source and the lithium source are mixed to form a positive electrode active material including the core part and the cladding layer, solving the problem of poor circulation performance of the nickel-manganese lithium material, and achieving process simplification, cost reduction and performance improvement.
Patent Information
- Application Number
- CN202510171346.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-11
AI Technical Summary
During the charging and discharging process of lithium nickel manganate, the surface lattice oxygen release leads to structural changes, resulting in poor cycling performance of the battery, and the traditional doping and coating processes are complex and costly.
By mixing the nickel-manganese hydroxide precursor, the titanium source, the lanthanum source and the lithium source, one-time sintering treatment is obtained, a positive electrode active material including a core portion and a cladding layer is LiaNibMn(8-a-4b-4x)TixO4 and the cladding layer is Li3LaO3.
Doping and coating of lithium nickel manganate material is achieved in one step, shortening the process flow, reducing costs, improving the cycling performance of the battery, and ensuring the conductive properties of the positive electrode active material.
Smart Images

Figure CN119812183A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of batteries, and particularly to a positive electrode active material, a preparation method thereof, a positive electrode sheet, a battery, and an electrical device. Background Art
[0002] Lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), as a high-voltage positive electrode material, has a discharge platform as high as 4.7 V (vs. Li / Li + ), a specific energy exceeding 600 Wh / kg, and does not contain cobalt element, so it is relatively environmentally friendly and the cost is relatively low. Therefore, it has become one of the most promising next-generation high-voltage positive electrode materials for commercialization.
[0003] However, during the charge and discharge process of the lithium nickel manganese oxide material, oxygen is released from the surface lattice, resulting in structural changes, and further leading to poor cycle performance of the battery.
[0004] In the traditional technology, the lithium nickel manganese oxide material is modified by doping and coating methods. However, doping and coating need to be carried out in batches, the process is relatively complex, and the cost is relatively high. Summary of the Invention
[0005] Based on this, it is necessary to provide a positive electrode active material, a preparation method thereof, a positive electrode sheet, a battery, and an electrical device, in which the doping and coating of the lithium nickel manganese oxide material are completed in one step, the process flow is shortened, while ensuring the conductivity of the positive electrode active material, the cost is reduced, and the cycle performance of the battery is improved.
[0006] The first aspect of the present application provides a preparation method of a positive electrode active material, the preparation method comprising: mixing a nickel manganese hydroxide precursor, a titanium source, a lanthanum source, and a lithium source, and then performing a sintering treatment to obtain the positive electrode active material; wherein, the positive electrode active material includes a core part and a coating layer, the coating layer covers at least part of the surface of the core part, the core part includes Li a Ni b Mn (8-a-4b-4x) Ti x O4, 0 < a < 1, 0 < b < 1, 0 < x < 1.5, and the coating layer includes Li3LaO3;
[0007] The temperature of the sintering treatment is 920 °C to 970 °C.
[0008] In some embodiments, x satisfies: 0.012 ≤ x ≤ 0.03.
[0009] In some embodiments, the mass ratio of the nickel manganese hydroxide precursor, the titanium source to the lanthanum source is 1:(0.0033 - 0.0083):(0.0059 - 0.0094).
[0010] In some embodiments, the particle size ratio of the nickel-manganese hydroxide precursor to the titanium source is (250 to 1000):1.
[0011] In some embodiments, the particle size ratio of the nickel-manganese hydroxide precursor to the lanthanum source is (250 to 1000):1.
[0012] The second aspect of the present application provides a positive electrode active material prepared by using the preparation method provided in the first aspect above. The positive electrode active material includes: a core portion including Li a Ni b Mn (8-a-4b-4x) Ti x O4, where 0 < a < 1, 0 < b < 1, and 0 < x < 1.5; and a coating layer covering at least a part of the surface of the core portion, the coating layer including Li3LaO3.
[0013] In some embodiments, the thickness of the coating layer is 1 nm to 4 nm.
[0014] The third aspect of the present application provides a positive electrode sheet, which includes the positive electrode active material prepared by using the preparation method provided in the first aspect above, or the positive electrode active material provided in the second aspect above.
[0015] The fourth aspect of the present application provides a battery, which includes the positive electrode sheet provided in the third aspect above.
[0016] The fifth aspect of the present application provides an electrical device, which includes the battery provided in the fourth aspect above.
[0017] Compared with the traditional technology, the present application has at least the following beneficial effects:
[0018] The preparation method provided by the present application can obtain the positive electrode active material by only one sintering. The doping and coating of the lithium nickel manganate material are completed in one step, shortening the process flow, greatly reducing the cost. The thickness of the coating layer of the prepared positive electrode active material is relatively thin. Therefore, while ensuring the conductivity of the positive electrode active material, the contact area with the electrolyte is reduced, side reactions are reduced, and the cycle performance of the battery is improved.
[0019] The positive electrode active material provided by the present application uses the preparation method provided in the first aspect above. The prepared positive electrode active material modifies the lithium nickel manganate material by means of Ti 4+ doping and Li3LaO3 coating layer coating, inhibiting the surface lattice oxygen release of the lithium nickel manganate material during charge and discharge. At the same time, the thickness of the coating layer is relatively thin, ensuring the conductivity of the lithium nickel manganate material while reducing the contact area with the electrolyte, reducing side reactions, and improving the cycle performance of the battery. Description of the Drawings
[0020] Figure 1 A surface TEM test image of the positive electrode active material in Example 1 of the present application is provided.
[0021] Figure 2 The surface EDS-La test image of the positive electrode active material in Example 1 of the present application is provided.
[0022] Figure 3 A cross-sectional EDS-Ti test image of the positive electrode active material in Example 1 of the present application is provided. DETAILED DESCRIPTION
[0023] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.
[0024] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.
[0025] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0026] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0027] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0028] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0029] Unless otherwise specified, all steps of this application can be carried out sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) carried out sequentially, or may also include steps (b) and (a) carried out sequentially. For example, when it is mentioned that the method may further include step (c), it means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b), and (c), or may also include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.
[0030] Unless otherwise specified, the terms "comprising" and "including" mentioned in this application are open-ended and can also be closed-ended. For example, the "comprising" and "including" may mean that other components not listed may also be included or contained, or may only include or contain the listed components.
[0031] Unless otherwise specified, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) while B is true (or exists); or both A and B are true (or exist).
[0032] A first aspect of this application provides a method for preparing a cathode active material, the preparation method including: mixing a nickel-manganese hydroxide precursor, a titanium source, a lanthanum source, and a lithium source and then performing a sintering treatment to obtain the cathode active material.
[0033] Among them, the cathode active material includes a core part and a coating layer, the coating layer coats at least part of the surface of the core part, and the core part includes Li a Ni b Mn (8-a-4b-4x) Ti x O4, 0 < a < 1, 0 < b < 1, 0 < x < 1.5, and the coating layer includes Li3LaO3.
[0034] The temperature of the sintering treatment is 920 °C to 970 °C.
[0035] In the method for preparing a cathode active material provided by this application, the ionic radius of Ti 4+ is 0.065 nm, which is smaller than that of La 3+The ion radius is 0.118nm. During the sintering treatment, the sintering temperature is controlled to melt the raw materials. Under the action of kinetics, the Ti element tends to be body-centered doped to improve the structural stability of the positive electrode active material, and the La element tends to be enriched on the surface of the lithium nickel manganese oxide material and combines with the lithium ions in the lithium source to form a Li3LaO3 coating layer. Therefore, the preparation method provided in the present application can obtain the positive electrode active material by only one sintering. The doping and coating of the lithium nickel manganese oxide material are completed in one step, which shortens the process flow and greatly reduces the cost. The coating layer of the prepared positive electrode active material is thin, so it can reduce the contact area with the electrolyte while ensuring the conductive performance of the positive electrode active material, reduce side reactions, and improve the cycle performance of the battery.
[0036] Furthermore, x satisfies: 0.012≤x≤0.03.
[0037] Illustratively, the temperature of the sintering process includes, but is not limited to, 920°C, 930°C, 940°C, 950°C, 960°C, and 970°C.
[0038] In some embodiments, the sintering process is a single sintering process.
[0039] In some embodiments, the sintering time is 10 h to 20 h. For example, the sintering time includes but is not limited to 10 h, 12 h, 14 h, 16 h, 18 h, and 20 h.
[0040] In some embodiments, the mass ratio of the nickel manganese hydroxide precursor, the titanium source, and the lanthanum source is 1:(0.0033-0.0083):(0.0059-0.0094). Exemplarily, the mass ratio of the nickel manganese hydroxide precursor, the titanium source, and the lanthanum source includes but is not limited to 1:0.0033:0.0094, 1:0.005:0.007, and 1:0.0083:0.0059.
[0041] In some embodiments, the particle size ratio of the nickel manganese hydroxide precursor to the titanium source is (250-1000): 1, and the particle size ratio of the nickel manganese hydroxide precursor to the lanthanum source is (250-1000): 1. Exemplarily, the particle size ratio of the nickel manganese hydroxide precursor to the titanium source includes but is not limited to 250: 1, 300: 1, 600: 1, 900: 1, 1000: 1, and the particle size ratio of the nickel manganese hydroxide precursor to the lanthanum source includes but is not limited to 250: 1, 300: 1, 600: 1, 900: 1, 1000: 1.
[0042] Specifically, the particle size of the nickel manganese hydroxide precursor is 5 μm to 10 μm, the particle size of the titanium source is 10 nm to 20 nm, and the particle size of the lanthanum source is 10 nm to 20 nm. Exemplarily, the particle size of the nickel manganese hydroxide precursor includes but is not limited to 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, the particle size of the titanium source includes but is not limited to 10 nm, 13 nm, 15 nm, 18 nm, 20 nm, and the particle size of the lanthanum source includes but is not limited to 10 nm, 13 nm, 15 nm, 18 nm, 20 nm.
[0043] It can be understood that by reducing the particle size of the titanium source and the lanthanum source, the melting of the titanium source and the lanthanum source can be effectively accelerated, which is conducive to forming good doping and continuous coating.
[0044] In some embodiments, the titanium source is selected from titanium oxide (TiO2) and La4Ti5O 12 One or more of .
[0045] In some embodiments, the lanthanum source includes lanthanum oxide (La2O3).
[0046] In some embodiments, the lithium source is selected from one or more of lithium hydroxide (LiOH) and lithium carbonate (Li2CO3).
[0047] In some embodiments, after the nickel manganese hydroxide precursor, titanium source, lanthanum source and lithium source are mixed and sintered to obtain the positive electrode active material, the method for preparing the positive electrode active material further includes: preparing the nickel manganese hydroxide precursor.
[0048] In some embodiments, preparing a nickel manganese hydroxide precursor specifically comprises the following steps:
[0049] S1. prepare a mixed solution of manganese salt / nickel salt, an aqueous ammonia solution and a sodium hydroxide solution.
[0050] The molar ratio of manganese salt to nickel salt is 3:1, the molar concentration of manganese salt in the mixed solution of manganese salt / nickel salt is 0.1 mol / L to 2 mol / L, the molar concentration of ammonia solution is 2 mol / L to 5 mol / L, and the molar concentration of sodium hydroxide solution is 2 mol / L to 5 mol / L.
[0051] S2. The mixed solution of manganese salt / nickel salt, aqueous ammonia solution and sodium hydroxide solution are simultaneously pumped into the reaction kettle through a peristaltic pump for reaction and aging.
[0052] The reaction temperature is 50° C. to 70° C., the pH of the reaction solution is 8 to 10.5, the reaction is carried out under a nitrogen atmosphere, and the aging time is 10 h to 15 h.
[0053] S3. Centrifuge, wash, and dry the aged slurry to obtain a nickel-manganese hydroxide precursor.
[0054] In some embodiments, the particle size of the nickel-manganese hydroxide precursor is controlled by controlling the reaction time.
[0055] In some embodiments, the nickel salt is selected from one or more of nickel sulfate, nickel nitrate, and nickel halides.
[0056] In some embodiments, the manganese salt is selected from one or more of manganese sulfate, manganese nitrate, and manganese halides.
[0057] The second aspect of the present application provides a positive electrode active material prepared by using the preparation method provided in the first aspect above. The positive electrode active material includes a core portion and a coating layer. The core portion includes Li a Ni b Mn (8-a-4b-4x) Ti x O4, where 0 < a < 1, 0 < b < 1, and 0 < x < 1.5. The coating layer coats at least a part of the surface of the core portion, and the coating layer includes Li3LaO3.
[0058] The positive electrode active material provided by the present application is prepared by using the preparation method provided in the first aspect above. The prepared positive electrode active material modifies the lithium nickel manganese oxide material by means of Ti 4+ doping and coating with a Li3LaO3 coating layer, which inhibits the release of oxygen from the surface lattice of the lithium nickel manganese oxide material during charge and discharge. At the same time, the thickness of the coating layer is relatively thin, which ensures the conductivity of the lithium nickel manganese oxide material while reducing the contact area with the electrolyte, reducing side reactions, and improving the cycle performance of the battery.
[0059] Further, x satisfies: 0.012 ≤ x ≤ 0.03.
[0060] In some embodiments, the thickness of the coating layer is 1 nm to 4 nm. Exemplarily, the thickness of the coating layer includes, but is not limited to, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, and 4 nm.
[0061] In some embodiments, the coating layer continuously coats the surface of the core portion.
[0062] The third aspect of the present application provides a positive electrode plate, which includes the positive electrode active material prepared by using the preparation method provided in the first aspect above, or the positive electrode active material provided in the second aspect above.
[0063] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer provided on the surface of the positive electrode current collector.
[0064] In some embodiments, the positive electrode active material accounts for 78% to 99% of the positive electrode active material layer by mass. Further, the positive electrode active material accounts for 90% to 99% of the positive electrode active material layer by mass.
[0065] In some embodiments, the positive electrode current collector is selected from metal foil and composite current collector; the composite current collector has a sandwich structure similar to a sandwich, the middle polymer layer is mainly a polymer insulating resin and other materials, and the metal layer is deposited on both sides of the middle polymer layer by electroplating, chemical plating or other methods. Schematically, the polymer resin includes polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyetheretherketone, polyimide, polyamide, polyethylene glycol, polyamide-imide, polycarbonate, cyclopentane One or more of polyolefin, polyphenylene sulfide, polyvinyl acetate, polytetrafluoroethylene, polymethylene naphthalene, polyvinylidene fluoride, polyethylene naphthalate, polypropylene carbonate, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-co-chlorotrifluoroethylene), silicone, vinylon, polypropylene, polyethylene, polyvinyl chloride, polystyrene, polyether nitrile, polyurethane, polyphenylene ether, polyester, polysulfone and its derivatives, sodium carboxymethyl cellulose, styrene-butadiene rubber, fluorinated rubber, polyvinyl alcohol or polyvinylidene fluoride. The material of the metal layer is selected from at least one of aluminum, copper, nickel, cobalt, tungsten, tin, lead, iron, silver or gold. Further, the positive electrode current collector is aluminum foil.
[0066] In some embodiments, the positive electrode active material layer further includes a conductive agent, which plays a role in collecting microcurrent between the positive electrode active materials and between the positive electrode active materials and the positive electrode current collector.
[0067] In some embodiments, the conductive agent accounts for 1% to 10% by mass in the positive electrode active material layer.
[0068] In some of the embodiments, the conductive agent includes graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, super-P and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; metal powders, such as fluorocarbon powders, aluminum powders and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives, and from the aspect of improving conductivity, the conductive agent may preferably be super-P.
[0069] In some embodiments, the specific surface area of the conductive agent can be 80 m 2 / g~200m 2 / g, preferably 100m 2 / g~150m 2 / g.
[0070] In some embodiments, the positive electrode active material layer further includes a binder, which can play a role in binding the positive electrode active material and the conductive agent together; the binder accounts for 1% to 10% of the mass of the positive electrode active material layer.
[0071] In some embodiments, the binder includes a fiberizable binder. It is understood that the fiberizable binder means that the binder can be transformed from a granular state to a fiber state under a high shear force.
[0072] In some embodiments, the fiberizable binder is selected from at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene (PE), and polypropylene (PP). Further, the fiberizable binder is selected from at least one of polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).
[0073] In some of the embodiments, in order to further enhance the bonding effect of the positive electrode system, the positive electrode active material layer also includes a second binder; the second binder is selected from at least one of polyvinylidene fluoride, polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose (CMC), polyvinyl pyrrolidone (HPC), polyethylene (PE), polypropylene (PP), ethylene-propylene-diene monomer, styrene-butadiene rubber (SBR), and fluororubber (FKM).
[0074] In some embodiments, the positive electrode active material layer further comprises solid electrolyte powder for improving the ionic conductivity of the composite positive electrode. The present invention does not limit the type of solid electrolyte powder.
[0075] In some embodiments, the solid electrolyte powder is selected from at least one of oxide solid electrolyte powder, sulfide solid electrolyte powder and halide solid electrolyte powder; further, the solid electrolyte powder is selected from halide solid electrolyte powder.
[0076] In some embodiments, the mass percentage of the solid electrolyte powder in the positive electrode active material layer is 1% to 18%; further, the mass percentage of the solid electrolyte powder in the positive electrode active material layer is 5% to 18%.
[0077] In some embodiments, the thickness of the positive electrode active material layer may be 30 μm to 400 μm, for example 30 μm, 40 μm, 50 μm, 80 μm, 110 μm, 200 μm, 300 μm, 400 μm, preferably 50 μm to 110 μm.
[0078] The fourth aspect of the present application provides a battery, which includes the positive electrode plate provided by the third aspect above.
[0079] In some embodiments, the battery also includes an electrolyte, and the electrolyte includes a solvent and an electrolyte salt. The solvent includes at least one of an ether solvent, propylene carbonate and fluoroethylene carbonate. The electrolyte salt can be lithium hexafluorophosphate (LiPF6), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorophosphate (LiPO2F2), lithium bis(oxalate borate) (LiBOB), lithium bis(oxalate borate) (LiODFB), lithium difluorobis(oxalate phosphate) (LiODFP) or lithium tetrafluorooxalate phosphate (LiTFOP).
[0080] In some embodiments, based on the total mass of the electrolyte being 100%, the mass percentage of the electrolyte salt is 0.5% to 25%.
[0081] In some embodiments, the electrolyte further comprises an additive, wherein the additive comprises at least one of 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 4-methyl vinyl sulfate, propenyl sulfate, saturated phosphate compounds and unsaturated phosphate compounds, tris(trimethylsilane) phosphate, tris(trimethylsilane) borate, tris(triethylsilane) borate, succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid nitrile, and sebaconitrile.
[0082] In some embodiments, the battery further comprises a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer formed on the surface of the negative electrode current collector, wherein the negative electrode active material layer comprises at least a negative electrode active material and a binder.
[0083] In some of the embodiments, the negative electrode active material in the embodiments of the present application is not particularly limited, as long as it is a substance that can electrochemically absorb and release S-zone metal ions such as lithium ions, sodium ions, potassium ions, magnesium ions, etc., such as carbonaceous materials, metal compound materials, or their oxides, carbides, nitrides, silicides, sulfides, phosphides, etc. These substances can be used alone, or two or more can be used in combination.
[0084] In some of the embodiments, a carbon material can be selected as the negative electrode active material, and specifically one or more of the following can be selected: graphite, needle coke, amorphous carbon, a carbon-containing mesophase, carbon fiber, and a carbon material with a low degree of graphitization. Among them, graphite can include natural graphite, artificial graphite, and the like. In addition, materials obtained by coating them with carbon materials, such as amorphous carbon and graphitized materials, can also be used. Amorphous carbon includes, but is not limited to, particles obtained by firing the entire mesophase, and particles obtained by infusible treatment and firing of a carbon precursor. As carbonaceous particles with a low degree of graphitization, particles obtained by firing organic matter at a temperature generally below 2500°C can be cited.
[0085] In some embodiments, the non-metallic materials that can be used as negative electrode active materials also include silicon and its compounds, such as Si, SiO x (0≤x<2), since silicon-containing materials are prone to expansion, easy to fall off from the negative electrode current collector, and have poor conductivity, they are often mixed with carbon materials, such as a core-shell structure containing a carbon coating layer.
[0086] In some of the embodiments, metal elements and metal compounds can also be selected as negative electrode active materials, such as compounds containing metals or metalloids such as Li, Ag, Al, Bi, Cu, Ga, Ge, In, Ni, Pb, Sb, Si, Sn, Sr, and Zn.
[0087] In some embodiments, the mass percentage of the negative electrode active material contained in the negative electrode active material layer can be 80% to 99%, for example, 80%, 85%, 90%, 95%, 97%, 99%, etc., preferably 95%-97%.
[0088] In some embodiments, when the negative electrode active material is a non-metallic material such as a carbon material, the binder may be an aqueous binder such as one or more of sodium hydroxymethyl cellulose, styrene-butadiene latex, polyacrylic acid, acrylic copolymer, cyclodextrin, and the like.
[0089] In some embodiments, the negative electrode active material layer can be obtained by coating a negative electrode slurry on a negative electrode current collector and then drying the negative electrode slurry, wherein the negative electrode slurry includes at least a negative electrode active material and a binder. When an aqueous solvent is used as a liquid medium for forming the negative electrode slurry, a thickener is preferably used for slurrying, and the thickener can generally be used to adjust the viscosity of the slurry.
[0090] In some embodiments, the thickener in the examples of the present application can be one or more of the following: carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein and their salts, etc.
[0091] In some embodiments, the mass proportion of the thickener in the negative electrode slurry can be 0.1% to 5%, for example, 0.1%, 0.2%, 0.5%, 0.6%, 1%, 2%, 3%, 4%, 5%, etc., preferably 0.5% to 3%, and more preferably 0.6% to 2%.
[0092] A fifth aspect of the present application provides an electrical device, which includes the battery provided by the fourth aspect.
[0093] The electrical device of the present application is not particularly limited, and it can be any electrical device known in the prior art. For example, the electrical device can include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.
[0094] The present application will be further described below with reference to specific embodiments and comparative examples.
[0095] Example 1
[0096] This embodiment provides a method for preparing a positive electrode active material, a positive electrode active material, a positive electrode plate, and a battery.
[0097] Preparation method of positive electrode active material:
[0098] (1) Preparation of nickel manganese hydroxide precursor Ni 0.25 Mn 0.75 (OH)2:
[0099] S1. Prepare a mixed solution of manganese salt / nickel salt, an ammonia solution and a sodium hydroxide solution with deionized water.
[0100] The molar ratio of manganese salt manganese nitrate to nickel salt nickel nitrate is 3:1, the molar concentration of manganese salt in the mixed solution of manganese salt / nickel salt is 1.5 mol / L, the molar concentration of ammonia water is 2 mol / L; and the molar concentration of sodium hydroxide is 5 mol / L.
[0101] S2. The mixed solution of manganese salt / nickel salt, aqueous ammonia solution and sodium hydroxide solution are simultaneously pumped into a reaction kettle through a peristaltic pump for reaction and aging.
[0102] The reaction temperature was 55° C., the pH of the reaction solution was 10.2, nitrogen protection was introduced throughout the process, and the aging time was 12 h.
[0103] S3, centrifuging, washing and drying the aged slurry to obtain a nickel manganese hydroxide precursor.
[0104] (2) Preparation of positive electrode active material: The nickel manganese hydroxide precursor, titanium source TiO2, lanthanum source La2O3 and lithium source LiOH were mixed in a mass ratio of 1:0.005:0.007:0.238 and then sintered to obtain a positive electrode active material.
[0105] The sintering temperature is 940℃, the sintering time is 12h, and Ni 0.25 Mn 0.75 The particle size of (OH)2 is 6 μm, the particle size of TiO2 is 10 nm, the particle size of La2O3 is 20 nm, and the particle size of Ni 0.25 Mn 0.75 The particle size ratio of (OH)2, TiO2 and La2O3 is 600:1:2.
[0106] Positive electrode active material:
[0107] The positive electrode active material is prepared by the above-mentioned preparation method, and the positive electrode active material includes a core part and a coating layer, and the coating layer is coated on at least a part of the surface of the core part. The core part includes Li 0.5 Ni 0.5 Mn 1.48 Ti 0.02 O4, the coating layer includes Li3LaO3, and the thickness of the coating layer is 2.2nm.
[0108] like Figures 1 to 3 As shown, the positive electrode active material provided in this embodiment is doped with Ti 4+ of lithium nickel manganese oxide material, and a Li3LaO3 coating layer is formed on the surface.
[0109] Positive electrode:
[0110] The positive electrode active material, conductive agent Super-P and binder PVDF were weighed in a mass ratio of 90:5:5, mixed to obtain slurry, coated on aluminum foil to form a positive electrode active material layer, dried and rolled to obtain a positive electrode sheet.
[0111] Battery:
[0112] The positive electrode sheet, negative electrode sheet and separator prepared above were stacked, placed in an aluminum-plastic film, injected with liquid (EC:DMC=1:1 vol%) and then formed to prepare a battery.
[0113] Among them, the negative electrode plate includes negative electrode active material graphite, conductive agent Super-P, and binder PVDF, and the mass ratio of the three is 90:5:5.
[0114] Example 2
[0115] The preparation method of the positive electrode active material, the positive electrode active material, the positive electrode plate, and the battery provided in this embodiment are basically the same as those in Example 1, except that:
[0116] Preparation method of positive electrode active material:
[0117] In step (2), Ni 0.25 Mn 0.75 The mass ratio of (OH)2, TiO2 and La2O3 is 1:0.0083:0.006.
[0118] Positive electrode active material:
[0119] The thickness of the coating layer is 2.5 nm.
[0120] Example 3
[0121] The preparation method of the positive electrode active material, the positive electrode active material, the positive electrode plate, and the battery provided in this embodiment are basically the same as those in Embodiment 1, except that:
[0122] Preparation method of positive electrode active material:
[0123] In step (2), Ni 0.25 Mn 0.75 The mass ratio of (OH)2, TiO2 and La2O3 is 1:0.0032:0.0092.
[0124] Positive electrode active material:
[0125] The thickness of the coating layer is 1.9 nm.
[0126] Example 4
[0127] The preparation method of the positive electrode active material, the positive electrode active material, the positive electrode plate, and the battery provided in this embodiment are basically the same as those in Embodiment 1, except that:
[0128] Preparation method of positive electrode active material:
[0129] In step (2), Ni 0.25 Mn 0.75 The particle size of (OH)2 is 10 μm, the particle size of TiO2 is 10 nm, the particle size of La2O3 is 10 nm, and the particle size of Ni 0.25 Mn 0.75 The particle size ratio of (OH)2, TiO2 and La2O3 is 1000:1:1.
[0130] Positive electrode active material:
[0131] The thickness of the coating layer is 1.8 nm.
[0132] Example 5
[0133] The preparation method of the positive electrode active material, the positive electrode active material, the positive electrode plate, and the battery provided in this embodiment are basically the same as those in Embodiment 1, except that:
[0134] Preparation method of positive electrode active material:
[0135] In step (2), Ni 0.25 Mn 0.75 The particle size of (OH)2 is 5 μm, the particle size of TiO2 is 20 nm, the particle size of La2O3 is 20 nm, and the particle size of Ni 0.25 Mn 0.75 The particle size ratio of (OH)2, TiO2 and La2O3 is 250:1:1.
[0136] Positive electrode active material:
[0137] The thickness of the coating layer is 2.4 nm.
[0138] Example 6
[0139] The preparation method of the positive electrode active material, the positive electrode active material, the positive electrode plate, and the battery provided in this embodiment are basically the same as those in Embodiment 1, except that:
[0140] Preparation method of positive electrode active material:
[0141] In step (2), the sintering temperature is 920°C.
[0142] Positive electrode active material:
[0143] The thickness of the coating layer is 2.2 nm.
[0144] Example 7
[0145] The preparation method of the positive electrode active material, the positive electrode active material, the positive electrode plate, and the battery provided in this embodiment are basically the same as those in Embodiment 1, except that:
[0146] Preparation method of positive electrode active material:
[0147] In step (2), the sintering temperature is 970°C.
[0148] Positive electrode active material:
[0149] The thickness of the coating layer is 2.1 nm.
[0150] Comparative Example 1
[0151] This comparative example provides a positive electrode active material, a positive electrode plate, and a battery.
[0152] Positive electrode active material:
[0153] Lithium nickel manganese oxide material (Li 0.5 Ni 0.5 Mn 1.5 O4).
[0154] Positive electrode:
[0155] The positive electrode active material, conductive agent Super-P and binder PVDF were weighed in a mass ratio of 90:5:5, mixed to obtain slurry, coated on aluminum foil to form a positive electrode active material layer, dried and rolled to obtain a positive electrode sheet.
[0156] Battery:
[0157] The positive electrode sheet, negative electrode sheet and separator prepared above were stacked, placed in an aluminum-plastic film, injected with liquid (EC:DMC=1:1 vol%) and then formed to prepare a battery.
[0158] Among them, the negative electrode plate includes negative electrode active material graphite, conductive agent Super-P, and binder PVDF, and the mass ratio of the three is 90:5:5.
[0159] Comparative Example 2
[0160] This comparative example provides a method for preparing a positive electrode active material, a positive electrode active material, a positive electrode plate, and a battery.
[0161] Preparation method of positive electrode active material:
[0162] (1) Preparation of nickel manganese hydroxide precursor Ni 0.25 Mn 0.75 (OH)2:
[0163] S1. Prepare a mixed solution of manganese salt / nickel salt, an ammonia solution and a sodium hydroxide solution with deionized water.
[0164] The molar ratio of manganese salt manganese nitrate to nickel salt nickel nitrate is 3:1, the molar concentration of manganese salt in the mixed solution of manganese salt / nickel salt is 1.5 mol / L, the molar concentration of ammonia water is 2 mol / L; and the molar concentration of sodium hydroxide is 5 mol / L.
[0165] S2. The mixed solution of manganese salt / nickel salt, aqueous ammonia solution and sodium hydroxide solution are simultaneously pumped into a reaction kettle through a peristaltic pump for reaction and aging.
[0166] The reaction temperature was 55° C., the pH of the reaction solution was 10.2, nitrogen protection was introduced throughout the process, and the aging time was 12 h.
[0167] S3, centrifuge, wash and dry the aged slurry to obtain Ni 0.25 Mn 0.75(OH)2.
[0168] (2) Preparation of positive electrode active material: 0.25 Mn 0.75 (OH)2, titanium source TiO2 and lithium source LiOH are mixed in a mass ratio of 1:0.008:0.238 and then sintered to obtain a positive electrode active material.
[0169] The sintering temperature is 940℃, the sintering time is 12h, and Ni 0.25 Mn 0.75 The particle size of (OH)2 is 6 μm, the particle size of TiO2 is 10 nm, and the particle size of Ni 0.25 Mn 0.75 The particle size ratio of (OH)2 to TiO2 is 600:1.
[0170] Positive electrode active material:
[0171] The positive electrode active material is prepared by the above preparation method, and the positive electrode active material includes Li 0.5 Ni 0.5 Mn 1.48 Ti 0.02 O4.
[0172] Positive electrode:
[0173] The positive electrode active material, conductive agent Super-P and binder PVDF were weighed in a mass ratio of 90:5:5, mixed to obtain slurry, coated on aluminum foil to form a positive electrode active material layer, dried and rolled to obtain a positive electrode sheet.
[0174] Battery:
[0175] The positive electrode sheet, negative electrode sheet and separator prepared above were stacked, placed in an aluminum-plastic film, injected with liquid (EC:DMC=1:1 vol%) and then formed to prepare a battery.
[0176] Among them, the negative electrode plate includes negative electrode active material graphite, conductive agent Super-P, and binder PVDF, and the mass ratio of the three is 90:5:5.
[0177] Comparative Example 3
[0178] This comparative example provides a method for preparing a positive electrode active material, a positive electrode active material, a positive electrode plate, and a battery.
[0179] Preparation method of positive electrode active material:
[0180] (1) Preparation of nickel manganese hydroxide precursor Ni 0.25 Mn 0.75 (OH)2:
[0181] S1. Prepare a mixed solution of manganese salt / nickel salt, an ammonia solution and a sodium hydroxide solution with deionized water.
[0182] The molar ratio of manganese salt manganese nitrate to nickel salt nickel nitrate is 3:1, the molar concentration of manganese salt in the mixed solution of manganese salt / nickel salt is 1.5 mol / L, the molar concentration of ammonia water is 2 mol / L; and the molar concentration of sodium hydroxide is 5 mol / L.
[0183] S2. The mixed solution of manganese salt / nickel salt, aqueous ammonia solution and sodium hydroxide solution are simultaneously pumped into a reaction kettle through a peristaltic pump for reaction and aging.
[0184] The reaction temperature was 55° C., the pH of the reaction solution was 10.2, nitrogen protection was introduced throughout the process, and the aging time was 12 h.
[0185] S3, centrifuge, wash and dry the aged slurry to obtain Ni 0.25 Mn 0.75 (OH)2.
[0186] (2) Preparation of positive electrode active material: 0.25 Mn 0.75 (OH)2, lanthanum source La2O3 and lithium source LiOH are mixed in a mass ratio of 1:0.008:0.238 and then sintered to obtain a positive electrode active material.
[0187] The sintering temperature is 750℃, the sintering time is 12h, and Ni 0.25 Mn 0.75 The particle size of (OH)2 is 6 μm, the particle size of La2O3 is 20 nm, and the particle size of Ni 0.25 Mn 0.75 The particle size ratio of (OH)2 to La2O3 is 300:1.
[0188] Positive electrode active material:
[0189] The positive electrode active material is prepared by the above-mentioned preparation method, and the positive electrode active material includes a core part and a coating layer, and the coating layer is coated on at least a part of the surface of the core part. The core part includes Li 0.5 Ni 0.5 Mn 1.5 O4, the coating layer includes Li3LaO3, and the thickness of the coating layer is 14nm.
[0190] Positive electrode:
[0191] The positive electrode active material, conductive agent Super-P and binder PVDF were weighed in a mass ratio of 90:5:5, mixed to obtain slurry, coated on aluminum foil to form a positive electrode active material layer, dried and rolled to obtain a positive electrode sheet.
[0192] Battery:
[0193] The positive electrode sheet, negative electrode sheet and separator prepared above were stacked, placed in an aluminum-plastic film, injected with liquid (EC:DMC=1:1 vol%) and then formed to prepare a battery.
[0194] Among them, the negative electrode plate includes negative electrode active material graphite, conductive agent Super-P, and binder PVDF, and the mass ratio of the three is 90:5:5.
[0195] The batteries of the above-mentioned embodiments and comparative examples were subjected to electrochemical tests, and the test results are shown in Table 1.
[0196] Table 1
[0197]
[0198] As shown in Table 1, by comparing Examples 1 to 7 and Comparative Examples 1 to 3, it can be seen that the method for preparing the positive electrode active material provided in the present application can achieve the doping of Ti ions and the coating of Li3LaO3 with only one sintering, forming a thinner coating layer, so that the positive electrode active material has excellent conductive properties, reduces the contact area with the electrolyte, reduces side reactions, and improves the capacity retention rate of the battery while ensuring the gram capacity.
[0199] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0200] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the technical concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A method for preparing a positive electrode active material, characterized in that: include: A nickel manganese hydroxide precursor, a titanium source, a lanthanum source and a lithium source are mixed and sintered to obtain a positive electrode active material; Among them, the positive electrode active material includes a core part and a coating layer, the coating layer covers at least part of the surface of the core part, and the core part includes Li a Ni b Mn (8-a-4b-4x) Ti x O4, 0 < a < 1, 0 < b < 1, 0 < x < 1.5, and the coating layer includes Li3LaO3; The sintering temperature is 920°C to 970°C.
2. The method for preparing a positive electrode active material according to claim 1, characterized in that: The x satisfies: 0.012≤x≤0.
03.
3. The method for preparing a positive electrode active material according to claim 1, characterized in that: The mass ratio of the nickel manganese hydroxide precursor, the titanium source and the lanthanum source is 1:(0.0033-0.0083):(0.0059-0.0094).
4. The method for preparing a positive electrode active material according to claim 1, characterized in that: The particle size ratio of the nickel manganese hydroxide precursor to the titanium source is (250-1000):
1.
5. The method for preparing a positive electrode active material according to any one of claims 1 to 4, characterized in that: The particle size ratio of the nickel manganese hydroxide precursor to the lanthanum source is (250-1000):
1.
6. A positive electrode active material prepared by the preparation method according to any one of claims 1 to 5, characterized in that: include: Core, including Li a Ni b Mn (8-a-4b-4x) Ti x O4,0 <a<1,0<b<1,0<x<1.5; as well as A coating layer is coated on at least a portion of the surface of the core portion, and the coating layer includes Li3LaO3.
7. The positive electrode active material according to claim 6, characterized in that The coating layer has a thickness of 1 nm to 4 nm.
8. A positive electrode sheet, characterized in that: The invention comprises a positive electrode active material prepared by the preparation method according to any one of claims 1 to 5, or a positive electrode active material according to claim 6 or 7.
9. A battery, characterized in that: Including the positive electrode sheet as described in claim 8.
10. An electrical device, characterized in that: A battery comprising the battery of claim 9.